AICCRA SPnS report: Evidence and learnings from Ghana - Ofosu-ampong, Kingsley; Seidu, Hisham; Yeboah, Patricia Amankwaa; Obeng, Faustina Adomaa; Maguta, Job Kihara; Abera, Wuletawu (2025)
The AICCRA Smart Production and Soils (SPnS) Bundle Accelerator, jointly implemented by partnership of Alliance Bioversity International & CIAT, Kukobila Nasia Farms, Eagle Park Innovations and Farm Radio International, supporting climate-resilient agricultural transformation among smallholder farmers across 18 communities in Northern, Upper East, and Upper West Regions of Ghana. A community in Northern Ghana is a socially connected group of households living within a shared geographic area (ranges 500-2500 people)—often a village or neighbourhood—bound together by kinship networks, traditional authority, livelihood activities, and cultural identity. Members generally rely on each other for support, cooperate in farming and social events, and organize themselves under the leadership of chiefs, elders, or religious figures. The accelerator promotes climate-smart agriculture through demonstration plots, digital climate information services, improved seed systems, and mass media outreach, with a strong focus on women and youth inclusion. Spanning across 2025, the initiative directly supported 3,939 farmers to apply CSA practices, reached an estimated 748,246 individuals through radio programming, trained 288 Village-Based Advisors and 1,440 farmers on ISFM and maize–cowpea intercropping, and distributed 3,778 cowpea seed-drop kits. Digital advisory systems reached 2,709 farmers via the Ag-Innovation Data Hub (AIDH) and WhatsApp. Thirty radio episodes promoted CIS and CSA adoption, generating high listener engagement. Next phase priorities include scaling the use of personalised/localised digital advisory, post-harvest strengthening, data validation, and sustaining digital and community-based extension networks.